THE IMPACT OF PROMOTION ON ROOM OCCUPANCY RATE IN MESRA BUSINESS AND RESORT HOTEL SAMARINDA - Muhammad Fikry Aransyah; Fareis Althalets; Tuti Wediawati; Andini Sari (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2020)
Purpose: The purpose of this research is to test and analyze the effect of the development of room occupancy rates at the Mesra Business and Resort Hotel in Samarinda Research methods: Primary data obtained by conducting interviews with 70 respondents using a questionnaire— secondary data collected by conducting field observation. Data were analyzed using a simple linear regression method with the help of SPSS statistical software version 23. Results and discussions: The result showed that the promotion variables consisting of advertising, direct sales, sales promotion, publicity, and word of mouth simultaneously had a significant effect on room occupancy rates. Conclusion: The promotional mix variable has a positive and significant effect on the room occupancy rate variable or the consumer's decision to choose a place to stay at the Mesra Business and Resort Hotel.